Digitizing Land Certificates to Anticipate the Mafia and Realize Legal Certainty - Subekti, Rahayu; Putranto, Muqtadir Ghani (Faculty of Law, Universitas Pattimura, 2023)
Indonesia's growth toward the digital era can no longer be applied to achieve modernization in the land sector, starting with the application of electronic-based land services, particularly the digitization of land certificates. By implementing electronic-based land services, the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency's Regulation No. 1 of 2021 concerning Electronic Certificates seeks to modernize land registration to enhance measures of the community's access to public services and ease of doing business. The issue with this research is the factors that prevent establishing a program for digital certificate holders to preserve their legal and land rights. Technically speaking, electronic certificates are more secure than analog (manual) ones when it comes to security. This added value will benefit holders of electronic land certificates by reducing the likelihood of certificate fraud, preventing illegal land transactions like those carried out by land mafias, and making it easier to transact with land parcels.